Self-assembled patches in PtSi/n-Si (111) diodes. (May 2018) - Afandiyeva, I. M.; Altιndal, Ş.; Abdullayeva, L. K.; Bayramova, A. İ.
Abstract: Using the effect of the temperature on the capacitance–voltage ( C–V ) and conductance–voltage ( G/ω–V ) characteristics of PtSi/n-Si (111) Schottky diodes the profile of apparent doping concentration ( N Dapp ), the potential difference between the Fermi energy level and the bottom of the conduction band ( V n ), apparent barrier height ( Φ Bapp ), series resistance ( R s ) and the interface state density N ss have been investigated. From the temperature dependence of ( C–V ) it was found that these parameters are non-uniformly changed with increasing temperature in a wide temperature range of 79–360 K. The voltage and temperature dependences of apparent carrier distribution we attributed to the existence of self-assembled patches similar the quantum wells, which formed due to the process of PtSi formation on semiconductor and the presence of hexagonal voids of Si (111).